Penerapan model role playing untuk meningkatkan pengetahuan konsep bhineka tunggal ika pada kelas V sekolah dasar - Jenni Yarinap; Hasan Mahfud; Fadhil Purnama Adi (Universitas Sebelas Maret, 2020)
Abstract. This study aims to find out how are the learning outcomes of students before and after the application of the role playing method in Setono No.95 State Elementary School Surakarta academic year 2019/2020. The method used in this research is a descriptive qualitative method, using a Classroom Action Research approach. The research subjects of the research that will be carried out are me as a researcher, teacher, and fifth grade students of SD Negeri Sutono No.95 Surakarta Academic Year 2019/2020. The data needed in this study includes primary data and secondary data. Based on the results of the study it can be concluded that the application of role playing models in fifth grade students of SD Negeri Setono No.95 in Surakarta 2019/2020 Academic Year has succeeded in increasing the understanding of the concept of Unity in Diversity. This is demonstrated by the presentation of the comprehension of Unity in Diversity in the initial conditions, cycle I and cycle II that continues.and provide the benefits of a very good contribution to student activities namely activity,curiosity,and courage.